Low-concentration electrolyte suitable for prussian blue and hard carbon sodium-ion battery and application of low-concentration electrolyte
By developing low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries, the film-forming performance of sodium salt and the advantages of ester solvents are used to solve the problems of performance decay and safety risks of sodium ion batteries at high temperatures, and achieve the goal of achieving Excellent cycle stability and high temperature performance.
Patent Information
- Application Number
- CN202510027870.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Sodium ion batteries have problems such as rapid decline in performance, decomposition of electrolytes, intensified side reactions, increased safety risks and shortened cycle life at high temperatures.
Develop a low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries, using sodium salts with good film formation properties, combining ester organic solvents and co-solvents, optimize the interface chemical components and structure, and form excellent positive and negative electrodes. Interface mask.
Excellent cycle stability is obtained at room temperature, and excellent cycle performance is also shown at high temperatures of 55°C, which significantly improves the battery's high-temperature application capabilities and safety.
Smart Images

Figure CN119447476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries and applications thereof. Background Art
[0002] Lithium-ion batteries have been widely used in many key areas such as electric vehicles and electronic devices, which has led to an explosive growth in the demand for lithium resources. However, lithium resources are not only limited in reserves, but also extremely unevenly distributed. Domestic lithium resources are basically dependent on import channels, which leads to frequent and large price fluctuations. This situation has prompted the search for alternative battery technologies. Sodium and lithium belong to the same main group and have very similar chemical properties. In addition, sodium is abundant on the earth, cheap, and easy to recycle and utilize. Furthermore, the working principle of sodium-ion batteries has many similarities with that of lithium-ion batteries. For this reason, sodium-ion batteries have broad development space and have become the leader of the next generation of new energy. At the same time, sodium ions have a smaller Stoke's radius than lithium ions, which makes them migrate faster in electrolytes and can achieve good ionic conductivity at lower concentrations. In addition, the desolvation energy of sodium ions is low, which helps to release and embed ions more easily during the battery charging and discharging process, thereby improving the battery's charging and discharging efficiency and cycle stability.
[0003] Sodium salt in the electrolyte plays an indispensable role as an important component. It not only provides a certain amount of sodium ions for sodium-ion batteries, but also determines the transmission capacity of sodium ions in the electrolyte, affecting the charge and discharge cycle of the battery. In traditional concentration electrolytes (usually 1.0M), ionic conductivity usually changes with the change of electrolyte concentration. At lower concentrations, it increases with the increase of concentration, reaching a maximum value at 1.0M. Continuing to increase the concentration will cause more ions to aggregate and reduce the conductivity. Reducing the concentration of electrolyte salts to form low-concentration electrolytes will reduce the conductivity to a certain extent, but its rapid ion diffusion, low viscosity, good wettability, weak solvation energy and low cost make it have considerable application prospects in large-scale fields.
[0004] There are many problems with the current sodium-ion battery when used at high temperatures, such as rapid performance decay. High temperatures can cause the electrolyte to decompose rapidly, resulting in many side reactions. They can also accelerate the side reactions of the electrode materials, causing the battery capacity to decay faster. For example, the positive electrode material may undergo structural changes and phase changes, affecting the efficiency of sodium ion insertion and extraction. In addition, it will also bring serious safety risks. The chemical reaction activity inside the battery is enhanced under high temperature conditions, which may cause safety hazards such as thermal runaway. For example, the electrolyte may decompose to produce gas, causing the internal pressure of the battery to increase, and even explosions and fires may occur. The battery cycle life is shortened. High temperatures will accelerate the aging of various components inside the battery, causing the battery's cycle charge and discharge performance to decline and the cycle life to be greatly shortened. Self-discharge increases. Under high temperature conditions, some side reactions inside the battery will cause the self-discharge phenomenon to intensify. Even when not in use, the battery power will be lost quickly. Summary of the invention
[0005] In view of the above problems, the present invention has developed a low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries. The electrolyte uses sodium salt with good film-forming properties, which can form a good interface film at the positive and negative electrodes during formation. Compared with traditional electrolytes, the electrolyte has the following advantages: (1) better film-forming properties; (2) lower viscosity; (3) better wettability; (4) lower concentration; in addition, sodium ions have a smaller Stoke's radius and lower desolvation energy, and sufficient kinetic performance can be obtained at lower sodium salt concentrations. Further, by regulating the unique solvation structure of salts, solvents and co-solvents, the interface chemical components and structures are optimized. The present invention obtains excellent cycle stability when the sodium ion battery operates at room temperature, and obtains excellent cycle performance at a high temperature of 55°C.
[0006] The first object of the present invention is to provide a low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries, wherein the sodium ion battery electrolyte is an ultra-low concentration electrolyte, and the concentration of sodium salt in the ultra-low concentration electrolyte is 0.04-0.86 mol / L.
[0007] The sodium salt is one or more of sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalate borate, sodium dioxalate borate, and sodium difluorophosphate. The overall concentration of the sodium salt is 0.04-0.86 mol / L, further optimized to 0.1-0.2 mol / L.
[0008] The ester organic solvent is one or more of a chain carbonate solvent and a cyclic carbonate solvent, wherein the chain carbonate solvent includes dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, and the cyclic carbonate solvent includes ethylene carbonate and propylene carbonate. The volume ratio of the chain carbonate solvent to the cyclic carbonate solvent is 2:8 to 8:2.
[0009] The co-solvent is one or more of bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), tris(2,2,2-trifluoroethyl) orthoformate, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (HFE), 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether (OTE), and fluorobenzene. 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is preferred. The volume ratio of the carbonate solvent to the co-solvent is 3:2 to 9:1.
[0010] The low-concentration electrolyte of the present invention is prepared by the following method: at room temperature, in a glove box protected by nitrogen (O2<0.01ppm, H2O<0.01ppm), the sodium salt, the mixed solvent and the low-polarity co-solvent are mixed to obtain a clear and transparent solution.
[0011] The second object of the present invention is to provide the above-mentioned low-concentration electrolyte which can be applied to sodium ion batteries assembled with Prussian blue / hard carbon and applied at high temperatures of 55°C.
[0012] The low-concentration electrolyte is used to match the Prussian blue positive electrode active material.
[0013] The sodium ion battery comprises a positive electrode material, a separator, a negative electrode material and the above-mentioned low-concentration electrolyte.
[0014] Preferably, the charge and discharge window of the sodium ion battery is 2~3.6V.
[0015] Preferably, the conductive agent of the sodium ion battery is one or more of acetylene black, conductive carbon black Super P and carbon nanotubes; Preferably, the positive electrode sheet is prepared by mixing a positive electrode material (Prussian blue), a binder, and conductive carbon, adding a solvent to form a slurry, coating the slurry on a current collector, and then drying, rolling, and slicing the slurry; Preferably, the negative electrode sheet is prepared by mixing a negative electrode material, a binder, and conductive carbon, adding a solvent to form a slurry, coating the slurry on a current collector, and then drying, rolling, and slicing the slurry; The low-concentration electrolyte of the present invention can greatly reduce the amount of salt used, lower the production cost of the electrolyte, and is conducive to large-scale use.
[0016] The electrolyte of the present invention utilizes the excellent film-forming effect of sodium salt to improve the basic properties of the electrolyte, reduce its viscosity, improve the wettability to the diaphragm, regulate the solvation structure, construct an excellent positive and negative electrode interface film, and achieve excellent cycle stability and high temperature performance of the sodium ion battery.
[0017] The electrolyte of the present invention can achieve stable circulation on 18650 sodium ion cylindrical batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the ionic conductivity corresponding to different concentrations of electrolyte.
[0019] Figure 2 It is the cycling performance of the iron-manganese-based Prussian blue (FeMnHCF) ‖ HC full battery corresponding to different electrolyte concentrations.
[0020] Figure 3 It is the cycle performance of the iron-manganese-based Prussian blue (FeMnHCF) ‖HC full battery corresponding to the comparative example and the embodiment of the present invention at room temperature 25°C.
[0021] Figure 4 It is the cycle performance of the iron-manganese-based Prussian blue (FeMnHCF) ‖HC full battery at a high temperature of 55°C corresponding to the comparative example and the embodiment of the present invention.
[0022] Figure 5 The cycle performance of the 18650 cylindrical battery in the embodiment of the present invention is DETAILED DESCRIPTION
[0023] The present invention is described below by specific examples. The examples are provided to better understand the present invention and are not intended to limit the scope of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0024] Example 1 A method for preparing a low-concentration sodium ion battery electrolyte is as follows: In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.1mol / L to a mixed solvent of PC:EMC (propylene carbonate:ethyl methyl carbonate) in a volume ratio of 2:3. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0025] The battery assembly uses the above electrolyte, and the electrode production and battery assembly process are the same as above. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0026] Example 2 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.2mol / L to a mixed solvent of PC:EMC with a volume ratio of 2:3. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0027] The battery assembly uses the above electrolyte, and the pole piece is made in the same way as the battery assembly process. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0028] Example 3 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.5mol / L to a mixed solvent of PC:EMC with a volume ratio of 2:3. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0029] The battery assembly uses the above electrolyte, and the pole piece is made in the same way as the battery assembly process. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0030] Example 4 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.2mol / L to a mixed solvent of PC:EMC:TTE in a volume ratio of 4:4:2. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0031] The battery assembly uses the above electrolyte, and the pole piece is made in the same way as the battery assembly process. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0032] Example 5 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.2mol / L to a mixed solvent of PC:EMC:TTE in a volume ratio of 3:5:2. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0033] The battery assembly uses the above electrolyte, and the pole piece is made in the same way as the battery assembly process. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0034] Example 6 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium difluorooxalatoborate was added at a concentration of 0.2mol / L to a mixed solvent of PC:EMC:FB with a volume ratio of 3:5:2. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0035] The battery assembly uses the above electrolyte, and the pole piece is made in the same way as the battery assembly process. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0036] Comparative Example 1 In a nitrogen atmosphere glove box with a water content of <0.01ppm and an oxygen content of <0.01ppm, sodium perchlorate at a concentration of 1mol / L was added to a solvent with a PC:EMC volume ratio of 2:3, and 2wt% FEC was added. After complete dissolution, a clear liquid was obtained, which was allowed to stand and used as an electrolyte.
[0037] The battery assembly uses the above electrolyte, and the electrode production and battery assembly process are the same as above. The assembled battery is tested for charge and discharge at 25°C, and the battery is activated at a rate of 0.1C for the first two cycles, and then the battery is tested for charge and discharge at a rate of 0.5C. The charge and discharge range is 2~3.6V.
[0038] Table 1. Test results of charge and discharge performance at room temperature 25℃ Battery ID First charge specific capacity (mAh / g) First discharge specific capacity (mAh / g) First effect (%) 300 cycles capacity retention rate (%) Data Source Example 1 157.77 135.54 85.91 / Figure 2 Example 2 158.66 136.71 86.16 67.82 Figure 2 Example 3 160.78 137.28 85.39 57.13 Figure 2 Example 4 160.89 137.32 85.35 77.42 Figure 3 Example 5 159.75 137.88 86.31 87.73 Figure 3 Example 6 163.73 139.49 85.19 79.81 Figure 3 Comparative Example 1 160.56 135.84 84.60 64.77 Figure 3 Note: “ / ” indicates too bad, no test required It can be concluded from Table 1 that the low-concentration electrolyte prepared in Example 5 can make the sodium ion battery have better cycle stability than other electrolytes, and still has a capacity retention rate of 87.73% after 300 cycles at room temperature 25°C.
[0039] Table 2. Test results of charge and discharge performance at 55℃ Battery ID First charge specific capacity (mAh / g) First discharge specific capacity (mAh / g) First effect (%) 100 cycles capacity retention rate (%) Data Source Example 2 146.46 126.07 86.08 87.60 Figure 4 Example 4 157.14 133.59 85.02 89.61 Figure 4 Example 6 153.76 126.34 82.17 88.08 Figure 4 Comparative Example 1 157.13 123.56 78.63 81.48 Figure 4 From Table 2, it can be concluded that at a high temperature of 55°C, the first charge and discharge efficiencies of Examples 2, 4, and 6 are 86.08%, 85.02%, and 82.17%, respectively, while that of the comparative example is only 78.63%, indicating that the low-concentration electrolyte has a significant advantage over the comparative example 1 at a high temperature of 55°C.
[0040] Table 3 18650 cylindrical battery charge and discharge performance test results Battery ID First charge specific capacity (mAh / g) First discharge specific capacity (mAh / g) First effect (%) 100 cycles capacity retention rate (%) Data Source Example 2 925.9 754.9 81.53 99.14 Figure 5 Example 4 938.1 771.9 82.28 88.44 Figure 5 Example 6 929.5 748.00 80.48 / Figure 5 Note: “ / ” indicates too bad, no test required It can be seen from Table 3 that among the 18650 cylindrical batteries, Example 2 has excellent performance, and still has a capacity retention rate of up to 99.14% after 100 cycles.
[0041] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0042] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries, characterized in that: The electrolyte is prepared by mixing one or more sodium salts, an ester organic solvent and a low-polarity co-solvent, wherein the concentration of the sodium salt is 0.04-0.86 mol / L.
2. The low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 1, characterized in that: The sodium salt is one or more of sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, and sodium difluorophosphate.
3. The low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 1, characterized in that: The ester organic solvent is composed of one or more of a chain carbonate solvent and a cyclic carbonate solvent, wherein the chain carbonate solvent includes dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, and the cyclic carbonate solvent includes ethylene carbonate and propylene carbonate.
4. The low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 1, characterized in that: The co-solvent is one or more of bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), tris(2,2,2-trifluoroethyl) orthoformate, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (HFE), 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether (OTE), and fluorobenzene.
5. The low-concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 1, characterized in that: The volume ratio of the chain carbonate solvent to the cyclic carbonate solvent is 2:8-8:2, and the volume ratio of the carbonate solvent to the co-solvent is 3:2-9:
1.
6. A Prussian blue / hard carbon sodium ion battery with a low concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to any one of claims 1 to 5, characterized in that: The positive electrode plate, the separator, the low-concentration sodium-ion battery electrolyte and the negative electrode plate are assembled in sequence, and the sodium-ion battery is obtained through static and formation processes.
7. The Prussian blue / hard carbon sodium ion battery with a low concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 6, characterized in that: The positive electrode material is a Prussian blue analogue. The positive electrode sheet is prepared by mixing the positive electrode active material, a binder, and conductive carbon, adding a solvent to form a slurry, coating the slurry on the current collector, and then drying, rolling, and slicing the slurry.
8. The Prussian blue / hard carbon sodium ion battery with a low concentration electrolyte suitable for Prussian blue and hard carbon sodium ion batteries according to claim 7, characterized in that: The negative electrode material is a hard carbon material. The negative electrode sheet is made by mixing the negative electrode material, a binder, and conductive carbon, adding a solvent to make a slurry, coating it on a current collector, and then drying, rolling, and slicing it.
Citation Information
Patent Citations
Low-concentration electrolyte of lithium ion battery with lithium-rich positive electrode
CN116365022A
Low-concentration electrolyte and application thereof in low-temperature sodium-ion battery
CN116487709A
Long-circulation non-aqueous sodium-ion battery electrolyte and sodium-ion battery
CN119069792A